Challenges in the introduction of AGVS in production lines: Case studies in the automotive industry - Hrušecká, Denisa (2019)
Increasing customers´ requirements together with the current trend of digitization in the spirit of Industry 4.0 puts pressure on manufacturing companies to increase both the flexibility and the performance of their manufacturing and logistic processes. This work presents the challenges in the introduction of AGV (Automatically Guided Vehicles) technology in production lines through two case studies from two different countries, Portugal and the Czech Republic. Both companies are from the automotive industry. Case study research aims to explore and understand complex phenomena. The main purpose of this study is to investigate the limitations and necessary conditions that must be considered when implementing AGV technology for automating selected logistic processes. Based on the data collected through multiple observations, a three-phase methodology considering technological, organizational and safety aspects is proposed as the main output. The basic scheme also includes the proposal of some critical success factors and key performance indicators that should be monitored in order to evaluate the efficiency of implementing this technology in future projects.